Two further patients with the 1q24 deletion syndrome expand the phenotype: A possible role for the miR199–214 cluster in the skeletal features of the condition. (3rd September 2015) - Ashraf, Tazeen; Collinson, Morag N.; Fairhurst, Joanna; Wang, Rubin; Wilson, Louise C.; Foulds, Nicola
Abstract : Submicroscopic deletions within chromosome 1q24q25 are associated with a syndromic phenotype of short stature, brachydactyly, learning difficulties, and facial dysmorphism. The critical region for the deletion phenotype has previously been narrowed to a 1.9 Mb segment containing 13 genes. We describe two further patients with 1q24 microdeletions and the skeletal phenotype, the first of whom has normal intellect, whereas the second has only mild learning impairment. The deletion in the first patient is very small and further narrows the critical interval for the striking skeletal aspects of this condition to a region containing only Dynamin 3 ( DNM3 ) and two microRNAs that are harbored within intron 14 of this gene: miR199 and miR214 . Mouse studies raise the possibility that these microRNAs may be implicated in the short stature and skeletal abnormalities of this microdeletion condition. The deletion in the second patient spans the previously reported critical region and indicates that the cognitive impairment may not always be as severe as previous reports suggest. © 2015 Wiley Periodicals, Inc.